USM STRENGTHENS COLLABORATION WITH CZECH REPUBLIC UNIVERSITIES - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 6 May 2016 The ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato’ Dr. Omar Osman who is on an official working visit to a number of universities in the Czech Republic since last Tuesday, has signed several Memorandums of Understanding (MoU) to strengthen collaborations with the renowned universities there.